Ungarischer Wein im mittelalterlichen Preußen - Pósán, László (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2024)
Hungarian wine in medieval Prussia In the Middle Ages, Prussia imported wine from all of the wine-producing regions of medieval Europe, including Hungarian wine from the beginning of the 15th century. Sigismund of Luxembourg, King of Hungary, was the first one to send wine to the Teutonic Order, and the first shipment was soon followed by others. Thus, Hungarian wine not only appealed to Prussian consumers, but also created an immediate demand for it. During the 15th century, Hungarian wine became available on the Prussian markets, although never in great quantities. This was due to the fact that it was not considered a drink for everyday consumption, but a highly prestigious one to be served on special, festive occasions. The best wine in Hungary at the time was produced in the south, in the wine-growing region of Syrmia, which was described in the second half of the 15th century by the Italian humanist Galeotto Marzio as “so sweet that it would be difficult to find a match for it in the whole world”. The wines of the Syrmia region could be best compared to today’s Tokaj szamorodni and aszú, known as dessert wines.